The design and development of a 1.4 GHz VCO - Hsin, William Hii How; Kung, Fabian; Chet, Koo Voon (IEEE Xplore, 2005)
Microwave oscillators are devices that convert DC power to microwave energy sources. This paper presents the design and development of a 1.4 GHz voltage-controlled oscillator (VCO). The design is based on the principle of generating a negative resistance to compensate for the losses of a resonator. The oscillator is designed using varactor diode with frequency tuning capability.